The Role of Upper Body Motions in Stationary Ball-Kicking Motion: A Systematic Review - Junze Chen; Kerry Peek; Ross Howard Sanders; Jack Lee; Johnson Chun Yiu Pang; Kanchana Ekanayake; Allan Chak Lun Fu (Journal of Science in Sport and Exercise, 2026)
A ball-kicking motion requires a coordinated sequencing of all body segments for maximum ball release speed. Evidence of the role of upper body rotations and motor coordination during a ball-kicking motion is inconsistent among existing evidence. This study aimed to systematically review the role of upper body rotations on all modes of ball kicking and performance metrics. A comprehensive search of seven electronic databases from the inception was conducted. Studies reporting on the relationships between upper body rotation, and ball-kicking performance were included. From 1486 potentially relevant studies, we analysed 27 studies involving 457 participants. These studies encompassed instep soccer kicks ( n = 21), inside-of-the-foot soccer kicks ( n = 1), rugby place kicks ( n = 4) with a stationary ball, and a volley kick ( n = 1). Methodological quality assessment was performed using Standard Quality Assessment Criteria. Our results provide moderate evidence that increasing thoracolumbar rotations along the longitudinal axis and the transverse plane can enhance ball-releasing velocity through a "whip-like effect" based on the kinetic link principle. However, to gain a comprehensive understanding, further research is needed to explore the effects of timing and the ranges of motion of all relevant upper and lower body segments on ball release velocity and its potential influence on ball release accuracy. The current coaching manuals do not emphasise the significance of upper body rotation, indicating a pressing requirement for revisions in training guidelines to enhance ball-kicking performance.

Immune divergence in rainbow trout lines selectively bred for F. psychrophilum resistance or susceptibility revealed by challenge with Weissella tructae - Gregory D. Wiens; Christopher C. Chadwick; Keira Osbourn; Qin Fu; Ross M. Reid; Travis Moreland; Timothy J. Welch; Timothy D. Leeds; David P. Marancik (Fish & Shellfish Immunology, 2026)

Recognition and Knowledge of Medications with Black Box Warnings Among Pediatricians and Emergency Physicians - Craig Geoffrey Smollin; Jonathan Fu; Ross Levin (Journal of Medical Toxicology, 2016)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

Insulin 3: From chemical synthesis to biological function - Ping Fu; Ross A. D. Bathgate; Geoffrey W. Tregear; John D. Wade (International Journal of Peptide Research and Therapeutics, 2003)

Allozyme Variation Patterns and Multiple Hybridization Origins: Clonal Variation Among Four Sibling Parthenogenetic Caucasian Rock Lizards - Jinzhong Fu; Ross D. MacCulloch; Robert W. Murphy; Ilya S. Darevsky; Boris S. Tuniyev (Genetica, 2000)

Old age, multiple formations or genetic plasticity? Clonal diversity in the uniparental Caucasian rock lizard, Lacerta dahli - Robert W. Murphy; Ilya S. Darevsky; Ross D. MacCulloch; Jinzhong Fu; Larissa A. Kupriyanova; Darlene E. Upton; Felix Danielyan (Genetica, 1997)

Disjunct habitats as islands: genetic variability in the Caucasian rock lizard Lacerta portschinskii - Ross D. MacCulloch; Robert W. Murphy; Jinzhong Fu; Ilya S. Darevsky; Felix Danielyan (Genetica, 1997)